Food-dependent exercise-Induced anaphylaxis - de Oliveira, Erick Prado [UNESP]; Burini, Roberto Carlos [UNESP] (My University, 2013)
The increase in sympathoadrenal activity is of major importance for the cardiovascular adaptation, thermoregulation and energy-yielding substrate in exercise. During exertion the blood flow to splanchnic organs is drastically reduced inducing changes in nutrient absorption, motility and mucosal integrity of the gastrointestinal (GI) tract. This reduced GI blood flow makes the gut mucosa susceptible to ischaemic injury, increases permeability and enhances occult blood loss as well as translocation of protective microbials and generation of endotoxins. Vigorous exercise and gut injury also facilitates allergen absorption from GI tract. Systemic reaction to exercise or 'physical allergy' occur in two distinct forms: cholinergic urticaria and exercise induced anaphylaxis (EIA). Symptoms of the former are usually limited to the skin whereas patients with EIA may present with a more severe systemic reaction. Food-dependent exercise-induced anaphylaxis (FDEIA) is a subtype of EIA and is related to prior consumption of food followed by exercise or other physical activity. Aspirin, nonsteroidal anti-inflammatory drugs, alcohol and menstruation are recognized cofactors. It has been suggested that exercise could increase basophil activation and histamine release by the increased osmolality, as well as trigger mast cell degranulation by decreased plasma pH. FDEIA can be of two subtypes - 'Specific FDEIA' relates to development of systemic reaction/anaphylaxis when consumption of a specific food allergen is followed by exercise as opposed to 'non-specific FDEIA', where symptoms can appear after any meal followed by exercise, i.e., regardless the food eaten. 'Specific FDEIA' has been associated with cereals, seafood, peanut, eggs, milk and vegetables. Careful clinical history is 'key' to diagnosis of EIA and FDEIA. Management involves counseling patients regarding the condition, relevant avoidance measures and provision of written emergency treatment plan for anaphylaxis. © 2013 Nova Science Publishers, Inc.